Role of Satisfaction with Life, Sex and Body Mass Index in Physical Literacy of Spanish Children - Javier Urbano-Mairena; María Mendoza-Muñoz; Jorge Carlos-Vivas; Raquel Pastor-Cisneros; Antonio Castillo-Paredes; Miguel Rodal; Laura Muñoz-Bermejo (MDPI AG, 2024)
Physical activity (PL) is essential to achieve good health, prevent cardiovascular diseases, obesity and overweight, as well as to achieve a better quality of life. Therefore, PL could become the tool to increase the practice of physical activity among young people, thus increasing life satisfaction (LS) given its positive relationship with physical activity. A single-measure cross-sectional correlational study was carried out, involving 135 children aged 8-12 years from Extremadura. They were administered the SWLS questionnaire and the Canadian assessment of physical literacy (CAPL-2). Significantly higher levels of PL (p = 0.010) were found in normal-weight children compared to overweight and obese children, due to the physical competence domain score (p < 0.001). PL was directly related to SWLS (p < 0.001), but inversely related to BMI (p = 0.018). The daily physical activity behaviour domain was explained by SWLS (p < 0.001) and sex (p < 0.001). Physical competence was described by SWLS (p < 0.001) and BMI (p = 0.045). Finally, the motivation and confidence domain were only significantly associated with SWLS (p < 0.001). It was concluded that boys and girls of normal weight achieved higher levels of PL and LS than those with overweight and obesity, establishing a negative relationship of PL with BMI and positive with LS.